Acceptability and feasibility of the online delivery of hatha yoga: A systematic review of the literature - Phoebe Brosnan; Maya Nauphal; Martha C. Tompson (Elsevier, 2021)
Objectives: Hatha yoga has dramatically increased in popularity in the United States and a growing body of evidence points to yoga's ability to successfully manage both physical and mental health conditions. Concurrently, the delivery of telehealth interventions also continues to rise. The online-delivery of yoga lies at this intersection, and to date, no study has systematically reviewed the existing literature of empirical studies involving the online delivery of yoga. Design: This study systematically reviews the literature for evidence on the feasibility and acceptability of online yoga interventions and provides a qualitative synthesis. A total of 10 articles which represent eight unique empirical studies were included in the final review. Results: Across the eight studies, participants expressed overall satisfaction with an online yoga intervention. Online yoga was found to be feasible, based on attendance and practice rates, and acceptable. Although groups vary in degree of initial engagement. Results also found preliminary evidence that online yoga can help manage symptoms associated with a range of disorders. Conclusions: Understanding this innovative approach to delivering yoga interventions will allow future research to include online yoga as a lower-cost, non-invasive intervention for a wide variety of physical and mental health disorders, as well as provide preliminary evidence to support the integration of online yoga interventions into routine clinical care.